Effects of constant load operations on platinum bands formation and cathode degradation in high-temperature polymer electrolyte fuel cells. (1st November 2018) - Liu, Shuai; Rasinski, Marcin; Lin, Yu; Wippermann, Klaus; Everwand, Andreas; Lehnert, Werner
Abstract: In this paper, Pt bands and cathode degradation are investigated in polybenzimidazole (PBI) membrane-based high-temperature polymer electrolyte fuel cells (HT-PEFC). A focused ion beam/scanning electron microscopy (FIB/SEM) system was used to characterize the cross-section morphologies of membrane electrode assemblies (MEA). A Pt band is observed in the FIB/SEM images of the MEA activated by a common break-in procedure (at 200 mA cm −2 for 70 h). Then, an identical MEA was subjected to an aging process that included static holding at 200 mA cm −2 for 100 h and an open circuit voltage (OCV) operation for another 100 h. FIB/SEM images of the aged MEA show that the band formed during the break-in procedure is strengthened. Moreover, a second Pt band is observed closer to the membrane/cathode interface, which is due to the increase of hydrogen crossover caused by membrane thinning during the OCV hold test. In situ electrochemical measurements show that the cell's performance loss due to the formation of the Pt band during cell operation at 200 mA cm −2 is negligible. The decrease of cell performance is mainly attributed to the loss of electrochemically active surface area and membrane degradation during the OCV hold test. Graphical abstract: Highlights: Cross-section morphologies of MEAs in HT-PEFCs were characterized by FIB/SEM. A Pt band is observed in the MEA activated by a common break-in procedure. The Pt band formed during OCV hold test shifts closer to cathode/membrane interface. The mechanism of Pt bands formation under different conditions is proposed. Cell's performance loss caused by the formation of Pt bands is evaluated.